Seismic responses of near-fault building clusters including in-plane rotational component in investigated lump model of earth medium. Issue 167 (April 2023) - Zhong, Wei; Liu, Tielin; Jiang, Yingchun; Qian, Bo
Abstract: An algorithm is proposed for modeling wave propagation with in-plane rotational component in earth medium. The proposed algorithm can not only carry out in-plane rotational wave propagation in half-space medium but also correctly undertake in-plane dynamic moment loading. Connecting ground and structure dynamically, a numerical method is given for implementing translational and rotational wave propagation in building clusters and earth medium caused by fault rupture. Three verification examples' results show correctness of the proposed algorithm in calculating ground responses due to a single vertical force, dynamic moment loading and finite-fault seismic sources, respectively. The seismic responses of near-fault building clusters are simulated during an M w 6.0 hypothetical earthquake. It is shown that in-plane rotational wave propagation in earth medium may increase significantly structural seismic responses. In all the three building clusters, the structural seismic response most affected by in-plane rotational wave propagation in earth medium is median bending moment (maximal increasing rate up to 163.0%), the second is inter-storey shear force (maximal increasing rate up to 37.5%) and the third is inter-storey drift (maximal increasing rate up to 24.2%). The existence of structural in-plane rotation can increase the horizontal displacements on the roof of buildings on the hanging wall and rupture forward of fault and decrease those on the footwall of fault. Altogether, the each-storey peak earthquake responses of one structure on hanging wall are larger than those of another identical structure on footwall at the same distance from fault-ground intersecting line. The contribution of rotational wave field in earth media and structures to structural responses should be considered in analyzing seismic responses of a city. Highlights: An algorithm is developed for simulating rotational wave propagation in earth medium. A numerical method is given for seismic responses of near-fault building cluster. The method can achieve rotational wave inter-propagation between site and structures.